Pengembangan Trainer Kendaraan Listrik Sederhana Sebagai Media Pembelajaran Pada Mata Pelajaran Dasar Otomotif di Jurusan Teknik Otomotif - Siswanto, Heri; Tuwoso, Tuwoso; Suhartadi, Syarif (Universitas Nahdlatul Ulama Blitar, 2024)
The purpose of this research is to create and develop a simple electric vehicle trainer as a learning medium in basic automotive subjects in the Department of Automotive Engineering. Knowing the level of feasibility, and knowing the effectiveness of simple electric vehicle trainers as a learning medium in basic automotive subjects. The research and development method used is the ADDIE model. Based on the results of data analysis, the percentage of eligibility of media experts was 88.45%, material experts were 83.65%, and the results of student responses in small group tests obtained a percentage of 97.95%. Thus, the development of a simple electric vehicle trainer is very feasible touse. Thus, the development of a simple electric vehicle trainer is very suitable for use as a learning medium for basic automotive subjects for the purpose of learning electric vehicles. From the results of the normality test, a sig value > 0.05 was obtained, so it was concluded that the data was normally distributed, so that a parametric statistical test was used, namely using the t-test. From the calculations it is known that the Asymp Sig (2 tailed) value is 0.000, so it can be said that there is a difference in the increase in learning outcomes for the experimental class compared to the control class. So, it can be concluded that there is an effect of increasing class learning outcomes that use the development of a simple electric vehicle trainer as a learning medium in basic automotive subjects for the purpose of learning electric vehicles.